Optimization and modeling of process parameters on the yield of enhanced pyrolysis oil during co-pyrolysis of cassava peel with polystyrene - B.S. Adeboye (Elsevier, 2021)
The co-pyrolysis of cassava peel (CP) and a synthetic waste, that is polystyrene (PS) has been investigated to optimize the yield of biofuel with improved properties. The main and interaction effects of process variables (temperature, feedstock ratio, and pyrolysis time) on the yield of pyrolysis oil were modeled and the optimal condition for enhanced pyrolysis oil yield was determined using response surface methodology by employing the central composite design matrix. A model equation was generated using the data obtained and the significance of the model was investigated using analysis of variance to determine if the fit of multiple regressions was significant. Some physical properties of the pyrolysis oil at the optimum condition were determined to investigate the suitability of the pyrolysis oil as a fuel source. From the statistical analysis, the study concluded that the feedstock ratio has the most significant effect on the yield of pyrolysis oil.